Integrated Planning of Public Passenger Transport between the City and the Region: The Case of Ljubljana - Bole, David; Gabrovec, Matej; Nared, Janez; Razpotnik Visković, Nika (Acta geographica Slovenica, 2012)
This article draws attention to the connection between transport planning and the settlement pattern and consequently the need for comprehensive planning of both the settlement and transport system. It primarily focuses on the suburbanization of Ljubljana and the state of public passenger transport in the Ljubljana Urban Region. Certain topical transport studies and measures are discussed from this perspective. The analysis shows the need for comprehensive planning that could be realized in the form of the concept of a polycentric layout of the region with interconnected centers as the main bearers of residential and business functions.